Global research profile on monkeypox-related literature (1962–2022): A bibliometric analysis - Sofyantoro, Fajar; Kusuma, Hendrix I.; Vento, Sandro; Rademaker, Marius; Frediansyah, Andri (Narra J, 2022)
The recent monkeypox or mpox outbreak has been a global concern. The present study evaluated the global research outputs, research trends, and topics of published research on monkeypox using a bibliometric approach. The Scopus database was searched for terms associated with "monkeypox" or "monkey pox" up until 19 November 2022. Maps and bibliometric indicators of the retrieved documents were shown and analyzed. A total of 1,422 documents were obtained from Scopus. Other than monkeypox, the most commonly used terms included epidemic, disease outbreaks, smallpox vaccine, and orthopoxvirus. In total, 90.3% of the documents were published between 2002 and 2022. The United States, the United Kingdom, and India were the top three countries in terms of productivity. Most of the institutions were from the United States. The International Journal of Surgery, the Journal of Medical Virology, and the Travel Medicine and Infectious Disease are some of the top journals currently publishing research on monkeypox. Tecovirimat, coronavirus disease 2019 (COVID-19), homosexuality, and pandemic are emerging topics related to monkeypox.